2005
DOI: 10.1143/jjap.44.l136
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Abrasive Size and Surfactant Concentration on the Non-Prestonian Behavior of Ceria Slurry in Shallow Trench Isolation Chemical Mechanical Polishing

Abstract: The propagation of a plane electromagnetic wave through a Lorentz plasma in a sheared magnetic field is considered. The characteristic waves in a uniformly sheared, but otherwise homogeneous, medium are found, and their properties presented graphically. Some effects introduced by the presence of shear are investigated by means of elementary applications of the uniform-shear theory. By suggested extensions of the analysis, refinements may be made in the interpretation of microwave diagnostic experiments with co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 9 publications
1
14
1
Order By: Relevance
“…When the applied pressure is increased, while maintaining the concentration of DADMAC, the ceria particles can penetrate through the adsorbed DADMAC layer and contact the oxide film surface. This is similar to the suggestion of Kang et al 15,16,46 and Shimono et al…”
Section: P39supporting
confidence: 93%
See 2 more Smart Citations
“…When the applied pressure is increased, while maintaining the concentration of DADMAC, the ceria particles can penetrate through the adsorbed DADMAC layer and contact the oxide film surface. This is similar to the suggestion of Kang et al 15,16,46 and Shimono et al…”
Section: P39supporting
confidence: 93%
“…Indeed, this DADMAC layer can prevent the interaction between the oxide surface being polished and the ceria abrasives as suggested by Kang et al 15,16,26 and Shimono et al 23 Also, while the adsorption of DADMAC on ceria particles is low and can be considered weak (see below), it can lower the oxide RRs if it reduces the number of reactive species on the ceria surface.…”
Section: Dadmac Adsorption On Siomentioning
confidence: 91%
See 1 more Smart Citation
“…Dishing takes place if the oxide material inside the trenches is polished, especially at the low pressures created by contact with the polishing pad. One efficient method that can minimize dishing is to use a non-Prestonian polishing slurry [5][6][7] which causes negligible removal below a threshold applied downward pressure. Recently, it was shown that a ceria-based slurry containing 15 mM diallyldimethyl ammonium chloride (DADMAC) as an additive resulted in non-Prestonian oxide removal 7 with negligible removal below ∼2 psi applied pressure.…”
mentioning
confidence: 99%
“…Zeta potential behavior of ceria in presence and absence of silicate ions[2] Zeta potential behavior of silicon nitride[3] Zeta potential behavior of Silica[4] …”
mentioning
confidence: 99%